Use of the bivalve Dreissena polymorpha as a biomonitoring tool to reflect the protozoan load in freshwater bodies. (1st March 2020) - Géba, Elodie; Aubert, Dominique; Durand, Loïc; Escotte, Sandy; La Carbona, Stéphanie; Cazeaux, Catherine; Bonnard, Isabelle; Bastien, Fanny; Palos Ladeiro, Mélissa; Dubey, Jitender P.; Villena, Isabelle; Geffard, Alain; et al.
Abstract: Cryptosporidium parvum, Toxoplasma gondii and Giardia duodenalis are worldwide pathogenic protozoa recognized as major causal agents of waterborne disease outbreaks. To overcome the normative process (ISO 15553/2006) limitations of protozoa detection in aquatic systems, we propose to use the zebra mussel ( Dreissena polymorpha ), a freshwater bivalve mollusc, as a tool for biomonitoring protozoan contamination. Mussels were exposed to three concentrations of C. parvum oocysts, G. duodenalis cysts or T. gondii oocysts for 21 days followed by 21 days of depuration in clear water. D. polymorpha accumulated protozoa in its tissues and haemolymph. Concerning T. gondii and G. duodenalis, the percentage of protozoa positive mussels reflected the contamination level in water bodies. As for C. parvum detection, oocysts did accumulate in mussel tissues and haemolymph, but in small quantities, and the limit of detection was high (between 50 and 100 oocysts). Low levels of T. gondii (1–5 oocysts/mussel) and G. duodenalis (less than 1 cyst/mussel) were quantified in D. polymorpha tissues. The ability of zebra mussels to reflect contamination by the three protozoa for weeks after the contamination event makes them a good integrative matrix for the biomonitoring of aquatic ecosystems. Graphical abstract: Image 1 Highlights: LOD95 and LOQ of protozoa by zebra mussel were defined. Methods are sensitive to detect T. gondii and G. duodenalis in zebra mussels. Percentage of positive mussels to protozoa could reflect protozoa loads in water. Quantification of protozoa in mussel is relevant to high protozoa level assessment. Zebra mussel can integrate past and present protozoa contamination.